Caudate volumes in childhood predict symptom severity in adults with Tourette syndrome - Bloch, Michael H. (2005)
BACKGROUND: Most children with Tourette syndrome (TS) experience a marked decline in the severity of tic symptoms during adolescence. Currently no clinical measures can predict whose tic symptoms will persist into adulthood. Previous cross-sectional imaging studies have identified reduced caudate nucleus volumes in subjects with TS. OBJECTIVE: To evaluate whether caudate nucleus volumes in childhood can predict the severity of tic or obsessive–compulsive symptoms at follow-up in early adulthood. METHODS: In a prospective longitudinal study, clinical status and basal ganglia volumes of 43 children with TS were measured on high-resolution magnetic resonance images before age 14 years. Follow-up clinical assessments were conducted after age 16 years, an average of 7.5 years later. Linear regression and Tobit regression analyses were used to assess the association of basal ganglia volumes measured in childhood with the severity of tic and obsessive–compulsive disorder (OCD) symptoms at the time of childhood MRI and at follow-up in early adulthood. RESULTS: Volumes of the caudate nucleus correlated significantly and inversely with the severity of tic and OCD symptoms in early adulthood. Caudate volumes did not correlate with the severity of symptoms at the time of the MRI scan. CONCLUSIONS: Caudate volumes in children with Tourette syndrome predict the severity of tic and obsessive–compulsive symptoms in early adulthood. This study provides compelling evidence that morphologic disturbances of the caudate nucleus within cortico-striatal-thalamo-cortical circuits are central to the persistence of both tics and obsessive–compulsive symptoms into adulthood.